KUALITAS RUNNING TEXT DALAM PEMBERIAN INFORMASI DI LINGKUNGAN KAMPUS SEKOLAH TINGGI TEKNOLOGI ADISUTJIPTO YOGYAKARTA - Septianto, Rivcky; Sumarsono, Sumarsono; Wintolo, Hero (Compiler, 2012)
Requirement about lectures information quickly, easily, accuratelly, and cheaply. To support lectures activity, such as lectures information scedules, lectures changed scedules, and the other informations based on running text with SMS Gateway in one way. In order to increase labor produktivity, data services, and information and increase computer skills in campus suroundings or college, that needs to be pursued in service enhancement effectively and efficiently, using information technology with running text based.In this application contains four interfaces, such as server application view, client application view, wireless fidelity (login hotspot) view, web view. Database design is a effort to make model of data management is still first draft. This database will be use to store data from the application.The result of whole research that can be analyze the test simulation is about mechanics work process from system over all. On the whole analyze result consist of the basic concept that built to become a system which has been discussed on the previous chapter.